An Analysis of the Legal Protection of Mineral and Coal Mining Activities in Indonesia which Impacts the Climate Around Mining Areas - Aqila Herdinyanto Sanjaya (CV. Rayyan Dwi Bharata, 2023)
The right to life and the right to welfare are two human rights that are often violated because of problems that hinder their protection and settlement in mining areas. Disputes arise when mining companies operate in an area, leading to social discord. How are mining permits issued in Indonesia? is the question posed at the heart of this thesis. and How does the law protect local residents from harm in mining areas? Philosophical strategies and enactment of moral laws are used in this research. Permits to operate mining companies in Indonesian territory are granted through a Mining Concession Work Agreement (PKP2B). Mining Business Permits (IUP), People's Business Permits (IUR), and Special Mining Business Permits (IUPK) are the three types of mining permits available in Indonesia. So that local communities and mining companies can work together and supervise each other, preemptive legal protection in the form of granting rights to local communities to manage and employ minerals and coal as well as the obligation to protect the ecosystem. Mining companies must be aware of their rights over natural resources, including dues, land payments, and reimbursement for the direct impacts of mining, even though an oppressive form of legal protection is that mining must be carried out on customary lands of indigenous peoples.